A legal study on telemedicine in Malaysia / Natasha Melissa Boyou...[et al.] - Boyou, Natasha Melissa; Andi Mansur, Saniayati; Syed Jaffar, Shariffah Raguan (2008)
This research is mainly concerns on law of telemedicine which form part of the cyber law in Malaysia. It deals with the associate legal problems concerning the practices of telemedicine in Malaysia namely the patient's right to confidentiality of medical information, the issue on regulating cost and medical malpractice of healthcare providers as well as its punishment. Apart from that, it also touches on the history and development of telemedicine itself. Telemedicine is still newly implemented in Malaysia under the Multimedia Super Corridor (MSC) which consists of four key pilot projects. This project proposed by the Health Ministry aims to provide better healthcare services towards the society. Therefore the purpose of this project is to find solutions as to how the patient's medical information will be kept secret in the absence of data protection laws; the legal positions regarding the medical malpractice of healthcare providers and to find out how the regulating cost or reimbursement is being addressed. Besides that this research will also look into the practice of telemedicine in other countries like United States, Japan and European countries. Furthermore it will examines on how they address all the issues concerning telemedicine The methodology used in this research is divided into three categories namely library-based research, internet search and interview. Literature review on textbooks, articles and journals are the paramount consideration in this study since it provides better views in order to understand the arising issues on telemedicine. The materials used in this study are mainly textbooks, articles, statutes, journals and cases.